Comparative Analysis of International Ranking Systems for Universities - Roxana-Adriana Mechno; Cristian-Vasile Doicin; Gabriel Petrea; Diana Scurtu; Alexandru-Ionut Buzatu (Communications of International Proceedings, 2020)
In the last years, higher education institutions have joined the top international rankings to "measure" their performance, through comparisons. The aim of this study is to identify the main indicators and criterions that international rankings pursue to classify the universities around the world. Moreover, this study also proposes to identify the similarities and/or differences among the rankings. At the same time, where similarities will be identified, a higher attention will be directed towards the indicator’s significance/magnitude. The study follows the impact of rankings that analyses higher education institutions which addresses larger fields such as research, technological innovation, the prestige of the institution etc. The study analyses five ranking systems, most relevant indicators, valuable input on the top of the first 10 universities for each ranking in 2019, provides the junction point of the 5 rankings taken into account and interprets the obtained results with respect to the context. Finally, based on the worldwide universities analysis, an overview on these classification and ranking systems will be obtained in order to provide a clearer general picture.
Keywords: Ranking; Higher Education; Research; Innovation